(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to analyze the record of dressings in the different Health Information Systems (Sistemas de Informação à Saúde-SIS). Method: it is a descriptive study, based on secondary data, in the period between 2017 and 2019. The data were extracted from open access systems and national coverage, among them: 1) Sistema de Gerenciamento da Tabela de Procedimentos, Medicamentos, Órteses, Próteses e Materiais Especiais-SIGTAP (Management System for the Table of Procedures, Drugs, Orthoses, Prostheses and Special Materials); 2) Sistema de Informação da Atenção Básica-SISAB (Primary Care Information System); 3) Sistema de Informação Ambulatorial-SIA/SUS (Ambulatory Information System). Results: 74,032,134 simple dressings were registered, of which 46.1% in 2017, 27.1% in 2018 and 26.7% in 2019. Regarding the grade II curative procedure with or without debridement, there were 11,559,664, with a value of approved of R 380,142,162.10. Of which 31.6% in 2017, 32.6% in 2018 and 35.8% in 2019. The name of the dressing procedure differs from Primary Care for the other levels of care, although in SISAB the dressings are called simple dressing and special dressing, both are related to the SIGTAP code: 0401010023 - Dressing Grade I. While in SIA/SUS the procedures related to dressing are 0401010023 - Dressing Grade I; and 0401010015 - Grade II dressing, making it difficult to compare procedures. In SIGTAP, the professional stoma nurse is qualified only to register a dressing 0401010023 - Grade I dressing, with or without debridement. Conclusion: the study reveals the need for revision of the SIS, due to inconsistencies of information, in addition to the SIS not communicating with each other. Thus, the completeness of the data needs to be considered, otherwise the knowledge generated may not represent reality.